Improved abrasion resistance of textile fabrics due to polymer coatings - Wortmann, Martin; Frese, Natalie; Hes, Lubos; Gölzhäuser, Armin; Moritzer, Elmar; Ehrmann, Andrea (Journal of Industrial Textiles)
Textile fabrics are often subject to abrasion, starting from exposed parts of garments to a variety of technical textiles. Abrasion protection by usual coatings, however, can significantly decrease the water vapor transport through a fabric which is often not desired, especially in the case of garments. In our paper, we report on an approach to combine increased abrasion resistance with sufficient water vapor transport properties. For this, different polymers (poly(methyl methacrylate), acrylonitrile butadiene styrene, or amorphous polyamides) were coated on cotton and polyester woven fabrics. The results of abrasion tests against sandpaper show significantly increased abrasion resistance. The absolute evaporation resistance, measured by a Permetest testing device, was only slightly increased up to values still acceptable for typical garments. Images of all coatings by helium ion microscopy deliver an explanation for the measuring results. Polymer coatings on the polyester fabric resulted in a slight reduction of the hydrophobicity, while coating the cotton fabric severely increased the contact angles of the originally superhydrophilic material.